Peningkatan Hasil Belajar Siswa Pada Pelajaran IPS Melalui Model Pembelajaran Kontekstual SDN 173265 Onan Hasang - Akbar, Muhammad Ali; Panggabean, Riris S. (Jurnal PGSD, 2024)
The low learning outcomes of fifth-grade students at SDN 173265 Onan Hasang were attributed to a lack of interest in learning, stemming from ineffective teaching methods that were not suitable for the subject matter. This research aimed to enhance students' abilities, learning outcomes, and activities in social studies (IPS), particularly in the topic of Indonesia's natural phenomena. A classroom action research (CAR) method was employed, targeting specific samples. The findings demonstrated the following: 1) Improvement in Learning Outcomes: The contextual teaching model effectively increased students' academic performance in social studies. 2) Content Relevance: Emphasis on local contexts, such as Indonesia's natural phenomena, engaged students by connecting the material to their environment. 3) Active Student Participation: The contextual learning model encouraged active involvement in the learning process. 4) Enhanced Critical Thinking Skills: Students showed improved critical and analytical thinking abilities through this approach. 5)Future Implications: The contextual teaching model presents an effective alternative for enhancing social studies education, particularly in understanding local environmental phenomena.